O specifiki vidnega sveta pri Dostojevskem in semantiki "videnj" v romanu Idiot - Krinicyn, Aleksandr B. (Slavistična revija, 2000)
The paper deals with the functions and meaning of neans fo visual presentation in F. M. Dostoevsky's novel Idiot. Attnetion is particularly focused on the functions and meanning of "visions". It includes visual presentations of "visions" of the mani literary characters (in particular of Duke Mishkin and Ippolit) in their direct "walking" contacts with people as well as in their dreams (particularly "professing") and hallucinatory dreams.
Keywords: Dostoevskij, Fedor Mihajlovič; Dostoevskij, Fedor Mihajlovič: Idiot; literarne študije; ruska književnost; semntika; tekstna lingvistika